Bunge's Rejection of Hegel, Husserl, and Heidegger and its Relation to Denialism (2022)
the philosopher Mario Bunge has been the most notable researcher of epistemology in our day. His preference for science and his rejection of pseudoscience are evident. Thus, it is recognized that Bunge's philosophy is analytical. Consequently, Bunge has also expressed his disagreement with those philosophies (mostly continental) that are unscientific or that have not promoted the study of science. In this way, the reasons why Bunge rejects Hegel, Husserl and Heidegger are analyzed. This rejection leads to an investigation of the bases of denialism and post-truth and, finally, a balance is made between Bunge's position and the flourishing of disinformation today.